OPTIMAL ORDERING AND PRICING ON CLEARANCE GOODS - Nakade, Koichi; Ikeuchi, Ken (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
In a food or convenience store, items such as meal and fresh foods must be sold within a few days. In this case, some old items are sold as clearance goods with a discounted price. In this study, a basic model with a fixed amount of orders is investigated where new and clearance goods are sold at the same time. First, the optimal ordering model is formulated when the discount price and selection probabilities are given. Next the optimal ordering and pricing model is formulated in the case that the discount retail price for clearance goods can be selected by a retailer and the amount of demand and selection probabilities for new and clearance goods depend on the discount price. The optimal number of orders and an optimal discount price are discussed through numerical experiments.